Marketing Business Integrity Café "Haus Indonesia" - Fitri, Novita Iza; Pradini, Gagih; Agustiani, Fitri; Rosdianti, Adella Syahrany; Kusumaningrum, Anisa Putri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Micro, Small and Medium Enterprises (MSMEs) make the largest contribution to the provision of employment. In 2021, MSMEs accounted for 97% of the total workforce in Indonesia. MSMEs are considered one of the sectors that play a very important role in the economic recovery process in Indonesia. MSMEs cover various sectors of job creation, such as culinary, agribusiness, clothing, and so on. Various innovations are created by business people to maintain their business amid fierce competition. In this era of globalization, one of the trending MSME sectors is Cafe/Tavern/Coffee Shop. This place is often visited by various ages, from children to teenagers, to adults. Usually, cafes or taverns provide facilities such as wifi, free chargers, and seating for visitors who order drinks, coffee, tea or food. Therefore, the café can be used as a place to discuss, chat casually or negotiate business. Currently, MSME Cafe or Tavern players, continue to innovate so that consumers become interested in products from their business brands. Business actors must also choose a good marketing strategy to manage marketing communication effectively so that a strong association is formed. Through these brand associations, it is expected to form brand awareness of the company's product brands.